Frequency of Occult Hepatitis C Virus Infection in the Spouses of Hepatitis C Virus Positive Patients - Abubakkar Alam, Zubair Ejaz, Muhammad Sohail, Kamran, Sadaf Abdullah, Asfand-E-Yar Khan, Bisma Khursheed, Inam Ullah, Syeda Rubina Gillani (Pakistan Journal of Medical & Health Sciences, 2023)
Hepatitis C is the major source of cirrhosis, HCC and chronic liver disease and is one of the major reasons for liver transplant and remain undiagnosed in large number of high-risk populations. Objectives: To assess the frequency of occult hepatitis C virus infection in the spouses of hepatitis C virus positive patients. Place and Duration: This Cross-sectional study was held in the Hepatitis clinic of gastroenterology ward of Lady Reading Hospital, Peshawar from 21st September 2020 till 20th March 2021 after approval from hospital ethical committee. Methods: Total 164 patients aged 20 to 60 years of both genders who were hepatitis C virus positive and whose spouses were healthy and asymptomatic were selected for this study. Frequency of occult hepatitis C infection in healthy spouse was determined. Data was analyzed and entered using SPSS 23. Results: In this analysis, total 164 patients were selected with mean age of 38.6±11.7 years. Among spouse history of previous surgery was present in 41.5%, history of blood transfusion in 47.6%, history of dental treatment in 73.2% and history of drug use in 54.9% sampled population. Frequency of occult hepatitis C infection was present in 7.3% healthy spouses. Conclusion: Hepatitis C infection is common in spouses of hepatitis C infection. All individuals presenting in OPD should be advised for spouse screening. Keywords: Occult, HCV, Intra-spousal transmission, intravenous drug use